Development of Practicum Module for Making Trimyristin Soap Active Ingredients from Nutmeg Seeds (Myristica fragrans Houtt) - Aliefman Hakim; Prapti Sedijani; Lalu Rudyat Telly Savalas; Saprizal Hadisaputra; Kukuh Waseso Jati Pangestu; Jono Irawan (Postgraduate, University of Mataram, 2023)
Research This aims to develop practicum module for making soap with natural active ingredients to improve students' creative thinking skills. Practicum instructions will be applied to natural science and natural product chemistry practicum courses to provide innovations and appropriate technology for science education master students. The development of practicum instructions is a Research and Development (R & D) development with a define, design, develop, and disseminate (4D) model. The samples of this research were chemistry students and Master of Science Education students. The tests carried out were tests of physical properties (organoleptic, pH, and homogeneity) and antimicrobial tests with varying concentrations of trimyristin. Products in the form of practicum module are validated. The results showed that the validity value of the three validators obtained using the Aiken index was V = 0.84, which indicated that the natural science practicum module: the procedure for making trimyristin soap from nutmeg, was very valid and feasible to use. Meanwhile, practicality can be seen from the responses of students and lecturers, who show a positive response with average practicality of all components of 88% of student responses and 89% of lecturer responses. The results of the physical evaluation of trimyristin solid soap (organoleptic, pH, foam stability, and moisture content) produced from this study showed good results because they met several standards for the quality of solid soap SNI 3532-2016. Based on these data, the materials chemistry practicum module: procedures for making trimyristin soap from nutmeg seeds to support meaningful learning that is developed is very valid and very practical to use in the learning process